Everyday Crafting of the Bolivarian State: Lower-level State Officials and Grassroots Activism in Venezuela. (January 2017) - Strønen, Iselin Åsedotter
Venezuela's communal councils are legally sanctioned organs for popular participation implemented mostly in poor communities since 2006. The promotores integrales, lower-level state employees who assist the communal councils in their everyday work, serve as mediators between state policies and community politics, and study of their roles and perspectives provides important insights into the complexities of implementing policies of popular participation and transforming state practices in the context of radical social change. While the cultural politics and knowledges of the popular sectors have become imprinted on the Venezuelan state, attempts to change the state in accordance with Bolivarian ideology are subject to intense contestation and struggle. Los consejos comunales de Venezuela son órganos para la participación popular establecidos legalmente y puestos en práctica mayormente en comunidades pobres desde 2006. Los promotores integrales –empleados estatales de menor rango que ayudan a los consejos comunales en su trabajo diario –sirven como mediadores entre las políticas del estado y la política comunitaria. El estudio de sus roles y perspectivas nos ofrece importantes claves para comprender la complejidad de implementar políticas de participación popular y transformar las prácticas del estado en el contexto de un cambio social radical. Mientras que las políticas culturales y los saberes de los sectores populares han quedado grabados en el estado venezolano, los esfuerzos para cambiar al estado de acuerdo con la ideología bolivariana están sujetos a una intensa impugnación y luchas constantes.